MERGER STRATEGY AND ITS EFFECTS ON PROFITABILITY FOR COMMERCIAL BANKS LISTED IN THE NSE IN KENYA - Warui, Stephen Kamau; Njeru, Phelista; Gongera, George; Bichanga, Julius (Machakos University, 2019)
For some of the commercial banks that are listed in the NSE in Kenya, merger strategy has been previously used, more-so to grow their profit margins. But for the past two decades, these commercial banks have been experiencing a lot of economic turbulence. The business environment has changed, which has led to an influx of banks in the country, the result of which is increased competition. This has not been made any simpler by the introduction of lowered interest rates in terms of loan-rates (a result of the government introducing the Capping Bill). Therefore, as an alternative strategy to closing down of branches and retrenching employees, this study seeks to find out if the re-use of merger strategy by these commercial banks will lead to a growth in profitability once again. The main objective of the study is therefore to analyze the effect of merger strategies on profitability of commercial banks listed in the NSE in Kenya. The research methodology used in the study was mixed research design methodology. The primary data was collected using questionnaires; while secondary data was collected from the audited financial statements. The researcher used purposive sampling in the study. The study was guided by the synergy-gains theory. In regard to correlation analysis being, it was observed that, merger strategy and ROA (after merger) had a positive and significant relationship. In regard to the regression analysis, the calculated p-value was 0.018, which was lower than the critical p-value of 0.05 for the study. This led to the researcher rejecting the null hypothesis that there was no significant relationship between merger strategy and profitability for commercial banks listed in the NSE. For primary data, using the five-point Likert scale, the responses average mean was found to be 3.75. This meant that, majority of the respondents agreed with the questions that were asked in the questionnaire for the study, which led to the conclusion that, merger strategies had significant effect on the profitability of commercial banks listed in the NSE. Therefore, a conclusion that the use of merger strategies by commercial banks listed in the NSE led to a growth in their profitability was drawn.
Keywords: Merger Strategy; Profitability; Nairobi Securities Exchange (NSE); Commercial Banks in Kenya